Gender and Body Mass Index-Related Serum Level of Adipokines and Metabolic Syndrome Components in Bipolar Patients who received Lithium and Valproic Acid - Marjani, Majid; Dolab, Neda; Kamkar, Mohammad Zaman; Amiriani, Taghi; Yuzugulen, Jale; Marjani, Abdoljalal (Mary Ann Liebert, Inc, 2021)
Background: This is the study to assess alterations on adiponectin, leptin, and metabolic syndrome components in women and men bipolar disorder (BD) patients with normal weight and obesity who received valproic acid (VPA) and lithium (Li).Methods: Thirty-six women and 51 men were included. Commercial kits were used to determine all parameters. Metabolic syndrome components were determined according to the NCEP ATP III criteria.Results: Patients who received Li and VPA significantly differ in waist circumference (WC) and triglyceride (TG) levels (in women and men). Normal weight patients received both drugs, significant differences were considered in high-density lipoprotein-cholesterol (HDL-C), WC, and TG levels compared to healthy controls, but there were significant differences in TG, leptin, and adiponectin levels in obese patients who received VPA. There were significant negative and positive correlation between leptin and adiponectin and WC and TG in women and men BD patients treated with VPA and Li. There were significant positive correlation between leptin and adiponectin and WC and TG and significant negative correlation with HDL-C in normal weight BD patients treated with VPA and Li, respectively, while there was only a significant positive correlation between leptin and adiponectin, and TG in obese BD patients treated with VPA.Conclusions: It looks like that patients treated with both drugs for our suggested time may increase leptin and adiponectin levels. Correlation differences between leptin and adiponectin, and metabolic syndrome components may be important parameters in women, men, normal weight, and obese BD patients. Monitoring of body composition and adipokines may benefit in medical care of these patients.
Keywords: gender; body mass index; adipokines; metabolic syndrome components; bipolar patients